ERP Customization as Software Engineering: Knowledge Sharing and Cooperation - Dittrich, Y.; Vaucouleur, S.; Giff, S. (IEEE software, 2009)
Enterprise resource planning (ERP) vendors provide multiple configuration possibilities ranging from module selection to master data provision to steer access rights for different users. These configuration possibilities cover anticipated variability. If the customer requires adaptation beyond what's anticipated, the source code of the product must be adapted. Customizations in this article's context are source code based adaptations of software products. The size and complexity of customizations range from simple report generation to developing independent add-ons that support specific businesses, for example, solutions for flight carriers. The size and lead time of such projects can compare to a full-size software development project. Enterprise resource planning (ERP) systems must be configured and customized to fit a specific company. The authors discuss cooperation with regard to ERP systems customization.